PENGARUH REPUTASI, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP MINAT MELAMAR PEKERJAAN OLEH MAHASISWA UNIVERSITAS UDAYANA - Permadi, Komang Dede; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 4 No 10 (2015), 2015)
The purpose of this research is to know the effect the reputation of the company, the compensation offered by the company and the company's work environment on the interest of applying for a job. This research was conducted on active student program extension 8th semester Faculty of Economics and Business, University of Udayana. Population at the object research amounted to 270 students and the sample of respondents amounted to 73 students. The sampling method using proportional random sampling method. Collecting data in this research is through observation, interviews and questionnaires. The analysis technique used in this research is multiple linear regression analysis. Based on the results of multiple linear regression analysis in this research (t test results) stated that the variable corporate reputation, the compensation offered by the company and the company's working environment partially positive and significant impact on the interest apply jobs.
Keywords: reputasi; kompensasi; lingkungan; minat melamar